(untitled) (JURNAL IBU DAN ANAK, 2021)
Low levels of hemoglobin in the blood can cause anemia. According to WHO, 40% of maternal deaths in developing countries are related to anemia in pregnancy caused by iron deficiency. In 100 grams of dragon fruit (Hylocereus Polyrhizus) contains 0.55-0.65 mg of iron and 8.00-9.00 mg of vitamin C. This type of research is a Quasy Experiment with one group pretest-posttest method. The sample of this study amounted to 20 pregnant women selected by purposive sampling technique. The results showed that the average Hb level of pregnant women before being given dragon fruit (Hylocereus Polyrhizus) was 12,250 (SD .8912) and after being given dragon fruit (Hylocereus Polyrhizus) the average Hb level of pregnant women was 13,600 (SD .6905). ). Based on the results of the T-dependent test, it was found that there was an effect of giving dragon fruit (Hylocereus polyrhizus) to hemoglobin levels in pregnant women (p = 0.000 (<0.05)). It is recommended for pregnant women to consume Dragon Fruit (Hylocereus Polyrhizus).